PELAYANAN BERWIRAUSAHA MASA PANDEMI COVID-19 HARUS DIDUKUNG DENGAN KEIKHLASAN DAN KETAQWAAN - nazirwan nazirwan (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The purpose of this article is to describe the challenges encountered by Indonesian people during Covid-19 pandemic, particularly on the economic fields as to seek for the alternatives for these problems. There are 3 problems identified. Firstly, it is how to embed and develop the entrepreneurial spirit. Secondly, it is how to conduct appropriacy study of entrepreneurial. The last one, it is about how to start and how to develop a business. In respond to this, government is implementing variety of policies and programs, such as: integrating education with entrepreneurial in each education levels, particularly on higher education level. It is due to entrepreneurial is considered as a way to reorganize economic and social mechanisms. Moreover, government also enhance lower and middle economic sectors in a national scale. This article also aimed to elaborate types of entrepreneurial that can be implemented along with their characteristics. Amongst the types of entrepreneurial that can be developed, namely, start up, creative industry, retailer business, and local business opportunity. As for the characteristics, namely, self-confidence, task and product oriented, risk taker, leadership, originality, and future-orientation. Furthermore, this article hinges on 4 key words, namely, entrepreneurial, service, sincerity, and devotion. Thus, each key word will be adequately elaborated along with numbers of theories, citation, and the like. In conclusion, it is highly expected that sincerity and devotion contributes positive and great advantages to the entrepreneurial service to allow Indonesian people to earn a better living in terms of economic and mindset particularly during Covid-19 pandemic.